Concert of the Vienna Philharmonic in Magdeburg, February 15, 1941 - Wiener Philharmoniker::::::::::::::: (Magdeburg; Germany, 2020)
Program of the Vienna Philharmonic, conducted by Hans Knappertsbusch, at the Stadthalle Magdeburg on February 15, 1941. The program included Beethoven's Seventh Symphony, op. 92.